Effect of personality traits on sensitivity, annoyance and loudness perception of low- and high-frequency noise. Issue 2 (June 2021) - Abbasi, Milad; Tokhi, Mohammad Osman; Falahati, Mohsen; Yazdanirad, Saeid; Ghaljahi, Maryam; Etemadinezhad, Siavash; Jaffari Talaar Poshti, Roghayeh
This paper presents investigations into a comparative assessment of the effects of low- and high-frequency noise in relation to personality traits. The high- and low-frequency noises used are produced in the research laboratory using CoolEdit software. In all, 80 candidates were exposed to equivalent continuous sound pressure level of 65 dBA of low- and high-frequency noise in an acoustic room with a 2-week interval. After 1 hour of exposure to noise, participants were asked to complete noise annoyance scale, Weinstein noise sensitivity questionnaire and loudness perception. The results obtained indicate that there is a significant difference between annoyance and perception of low-frequency noise in comparison to annoyance and perception of high-frequency noise, but no significant difference is noted between sensitivity to low- and high-frequency noise. The multivariate analysis of covariance test is applied, which reveals that personality traits have a significant effect on sensitivity to low- and high-frequency noise, annoyance due to low- and high-frequency noise, loudness perception of low-frequency noise, but no interaction effects are found. It is further shown that personality traits are more effective on sensitivity, annoyance and loudness perception to high-frequency noise than those of low-frequency noise, and such effects are not only influenced by severity of noise but also by personality traits and frequency components.